Investigation of the food poisoning outbreak in girls hostel of medical college in Punjab - Prajapati, Paresh; Kaur, Prabhjot; Sidhu, Tanvir K.; Singh, Gurkirat; Mehra, Shyam; Paul, Sourabh; Malhotra, Varun M.; ., Rupali (International Journal Of Community Medicine And Public Health, 2020)
Background: Food safety is intricately woven with food security and nutrition. The “in‑living personnel” constitute a high‑risk group for food poisoning because of community kitchen practices. Quick response and action are vital to limit the morbidity and spread of the disease. Methods: A retrospective cohort study was conducted to investigate the food poisoning outbreak in private medical college. After the initial information of the sudden cases of vomiting and diarrhoea from girls’ hostel, epidemiological case sheet was developed for collecting the information from students. A line listing of all the probable cases was done. Common food items were identified. An environmental data recording was done. Attack rate, attributable risk and relative risk with 95% confidence interval were calculated for each food item to establish an association with the illness. Results: Out of the 97 students, who consumed the dinner, 8 girls presented with severe symptoms of the gastrointestinal upset along with other bodily symptoms, 60 students showed mild symptoms and 29 students did not show any of the symptoms of the disease. After analysis, palak paneer was found to be the food responsible for outbreak with most probable cause of contamination with Staph auerus. Conclusions: It has been found out in this investigation that whenever the sanitation conditions of the cooking area were compromised and negligence was played at the part of food handlers - it has always increased the probability of such outbreaks and sufferings of the people.